Farm to Form : Modernist Literature and Ecologies of Food in the British Empire - Martell, Jessica (Book collections on Project MUSE., 2020)
"From farm to form: modernism, ecology, and the food politics of empire investigates the relationship between the rise of industrial food and the emergence of literary modernisms in Britain and Ireland. By weaving insights from modernist studies, food studies, and ecocriticism together, Farm to form contends that industrial food production transformed the natural world into a "modernist" terrain that shaped new literary forms, positioning modernism as central to the study of narratives of resistance against social and environmental degradation"--